Pengalihan Hak Asuh Anak Di Bawah Umur Kepada Ayah Biologis (Studi Putusan Nomor: 366/Pdt.G/2022/PA.Batg) - Retno Wulandari, Shelomita; Rosmidah, Rosmidah; Pahlefi, Pahlefi (Zaaken: Journal of Civil and Business Law, 2024)
The purpose of this study is to find out and analyze the transfer of child custody to the biological father after divorce based on the Compilation of Islamic Law and to find out and analyze the basis for the judge's consideration in granting a decision on custody of the minor to the biological father in decision number 366/Pdt.G/2022/PA.Batg. The problem in this thesis is how to transfer child custody to the father after divorce based on the Compilation of Islamic Law, and what is the basis for the judge's consideration in granting a decision on custody of a minor to the biological father in decision number 366/Pdt.G/2022/PA.Batg. The research method used is normative juridical research while the legal materials consist of primary, secondary and tertiary legal materials. The analysis of the collected legal materials is carried out by inventorying, and systematizing. The results of this thesis research contain the Bantaeng Religious Court deciding in case Number 366/Pdt.G/2022/PA.Batg to grant custody of the child to the applicant. Article 156 of the Compilation of Islamic Law stipulates that if the mother has passed away, the role of the mother can be replaced by women who have a direct kinship relationship from the mother's side. If it is found that there is negligence or instability of the person who has the right to have the hadhanah in taking care of his child, then the custody of the child can be transferred to his father. Meanwhile, adult children are given the freedom to choose between their father or mother as the holder of custody rights. However, the court considered that the decision had taken into account the interests of the child, so it handed over custody of the child to the father with proper legal considerations. In his consideration, the judge must make several considerations before giving a decision, the father has the opportunity to get custody of the minor if he meets several considerations from the judge by referring to the provisions in the Compilation of Islamic Law.